Didactic materials perception activating methods in distance education - Bukhkalo, Svetlana Ivanovna; Ageicheva, Anna Oleksandrivna; Belyanskiy, Oleksandr Mykolaiyvych; Rozhenko, Inesa Vitaliivna; Abakumov, Andrii Analoliyovych (Національний технічний університет "Харківський політехнічний інститут", 2024)
The article is devoted to the creation of didactic materials on various educational subjects at various levels of distance education. The relevance of the work is determined both by the object of research, which has not yet been subject to comprehensive scientific coverage, and by the need to establish the parameters of didactic materials used in distance learning. It was determined that the systematic usage of the innovative approaches improves language competence and formats necessary skills. The materials of the article consider examples the possibilities for determining the educational goals of university students for the purpose of developing the discipline Innovative restaurant technologies, Commodity science and procurement management for the development of complex projects. Developments are carried out using modern highly effective science-based technologies of food production, for example, from types of classification-identification analysis, general concepts and requirements to types of methodology for determining quality indicators of the quality level and their evaluation through the selection of calculation algorithms at various stages of production and use of the obtained goods. Стаття присвячена створенню дидактичних матеріалів з різних навчальних предметів на різних рівнях дистанційної освіти. Актуальність роботи зумовлена як об’єктом дослідження, який ще не підлягав комплексному науковому висвітленню, так і необхідністю встановлення параметрів дидактичних матеріалів, що використовуються в дистанційному навчанні. Визначено, що систематичне використання інноваційних підходів покращує мовну компетенцію та формує необхідні навички. У матеріалах статті на прикладах розглянуто можливості визначення освітніх цілей студентів ВНЗ з метою освоєння дисципліни «Інноваційні технології ресторанного господарства», «Товарознавство та управління закупівлями» для розробки комплексних проектів. Розробки ведуться з використанням сучасних високоефективних науковообґрунтованих технологій виробництва харчових продуктів, наприклад, від видів класифікаційноідентифікаційного аналізу, загальних понять і вимог до видів методології визначення показників рівня якості та їх оцінки шляхом вибору алгоритми розрахунку на різних етапах виробництва за технологічною схемою відповідно до нормативно-технічної документації з метою використання отриманої продукції.
Методи активізації сприймання дидактичних матеріалів в дистанційному навчанні
Keywords: distance education; didactic materials; innovative studies; project-oriented approach; pedagogy; innovative teaching approaches; дистанційна освіта; дидактичні матеріали; інноваційні дослідження; проектно-орієнтований підхід; інноваційні підходи; педагогіка